Wither the self-sufficiency illusion? Food security in Arab Gulf States and the impact of COVID-19 - Eckart Woertz (Food Security, 2020)
Past approaches to food security in the countries of the Gulf Cooperation Council (GCC) were informed by concerns about food availability. They aimed at domestic self-sufficiency and self-sufficiency by proxy (via farmland investments abroad). These strategies have failed. Water scarcity at home increasingly compromises agricultural production. Farmland investments abroad have not matched ambitious related announcements due to a complex mixture of commercial, socio-economic and political factors. They do not contribute meaningful quantities to the Gulf countries' food imports. The failure of such strategies has prompted a shift of focus instead towards value chain management as a means to secure food availability. Rather than trying to fight food import dependence, the Gulf countries now accept and manage it. However, malnutrition that leads to high levels of obesity and diabetes constitutes a risk factor in the face of COVID-19. Food accessibility for vulnerable population segments such as migrant labour is another issue that requires yet further policy measures, such as safety nets – whose expansion would be politically controversial if not impossible, however.
Keywords: 630; Middle East and North Africa; Food security; Land investments; Value chains; Safety nets